Sustainability in Open Distance Learning (ODL) Education: Canvassing the Right Market Segmentation and Effective Advertising Strategy - Mohd Nazri Mohd Noor,; Norsiah Aminudin,; Azlina Abdul Aziz,; Yanty Roslinda Harun,; Zulaikha Zakariah, (2021)
This paper addresses the perceptions that lead prospective learners’ to favour the right market segmentation and effective advertising messages in Open Distance Learning (ODL) advertisements. A descriptive study was conducted among the prospective ODL learners in Malaysia between January to March 2021. A self-administered questionnaire was utilised to gather data from 314 respondents throughout that period. Analysis of this study was conducted using SPSS Version 22 and SMART-PLS Version 3.2 to examine the reliability and validity of the questionnaire, thus, determining the significance of every independent variable and dependent variable in this research. The result obtained reveal that majority of the respondents give prominence to accessibility than substantiality between the ODL institution and market segment. On the other hand, the respondents place significance on the element of reminder and persuasive messages that received their attention towards the ODL institutions. The standardised path coefficients showed that accessibility, reminder and persuasive types of messages are the significant predictors of sustainability of ODL institutions whereby substantiality has been perceived by the respondents as not significant. Therefore, it is noteworthy to develop creative advertisements with emotional attachment in order to attract the audience’s attention and fit in the context of their opinions and beliefs. As a whole, the results from this study help the ODL institutions to be more focused in designing their advertising messages as well as understanding market needs. The findings have strong implications to both academic and the ODL institutions particularly in the aspect of institutional sustainability focusing on the effective market segmentation and the right strategy of advertising messages.